Piroxicam fails to reduce myocellular enzyme leakage and delayed onset muscle soreness induced by isokinetic eccentric exercise - J-L. Croisier; G. Camus; T. Monfils; G. Deby-Dupon; M. Fafchamps; I. Venneman; J-M. Crielaard; A. Juchmès-Ferir; C. Lhermerout; M. Lamy; C. Deby (Hindawi Limited, 1996)
To test the hypothesis that delayed onset muscular soreness (DOMS) following intense eccentric muscle contraction could be due to increased production of prostaglandin E2 (PGE2), ten healthy male subjects were studied. Using a double-blind randomized crossover design, each subject performed two isokinetic tests separated by a period of at least 6 weeks: once with placebo, and once with piroxicam (Feldene®). They were given one capsule containing either placebo or piroxicam (20 mg) per day for 6 days with initial doses given starting 3 days prior to isokinetic testing. Exercise consisted of eight stages of five maximal contractions of the knee extensor and flexor muscle groups of both legs separated by 1 min rest phases, on a Kin Trex device at 60°/s angular velocity. The subjective presence and intensity of DOMS were evaluated using a visual analogue scale immediately after, and 24 and 48 h after each test. The mean plasma concentration of PGE2 measured at rest and after exercise was significantly lower in the group treated with piroxicam (p < 0.05). However, statistical analysis (two-way ANOVA test) revealed that exercise did not cause any significant change of mean plasma PGE2 over time in either of the two groups. Eccentric work was followed by severe muscle pain in extensor and flexor muscle groups. Maximal soreness was noted 48 h postexercise. Serum creatine kinase activity and the serum concentration of myoglobin increased significantly, and reached peak values 48 h after exercise in both experimental conditions (p < 0.001). By paired t-test, it appeared that there were no significant differences in the serum levels of these two markers of muscle damage between the two groups at any time point. We conclude that: (1) oral administration of piroxicam fails to reduce muscle damage and DOMS caused by strenuous eccentric exercise; and (2) the hypothetical role of increased PGE2 production in eccentric exercise-induced muscle damage, DOMS, and reduced isokinetic performance is not substantiated by the present results.